Oncogenomics : from basic research to precision medicine - Dammacco, Franco; Silvestris, Franco (Elsevier Ltd. : Academic Press, 2019)
Oncogenomics: From Basic Research to Precision Medicine offers a thorough survey of precision medicine and its diagnostic and therapeutic applications in oncology. Gathering contributions from leading international researchers in the field, chapters examine recent translational advances in oncogenomic methods and technologies, detail novel molecular classifications of tumors, and identify diagnostic and prognostic biomarkers for various types of cancers, including pancreatic, gastrointestinal, breast, hematological, lung, osteotropic, genitourinary, and skin cancers. This book provides a foundation for clinical oncologists, human geneticists, and physicians to develop new targeted cancer treatments and incorporate genomic medicine into clinical practice.